VD_FINDINFO HC / 2010 / 686 vom 6. Oktober 2010 - VD Tribunal cantonal (2010)
CONTRAT D'APPRENTISSAGE, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, FAUTE PROPRE, INDEMNITÉEN GÉNÉRAL | 337 CO, 337c al. 3 CO, 346 al. 2 CO, 456a al. 1 CPC